2012
DOI: 10.1088/0004-637x/749/1/49
|View full text |Cite
|
Sign up to set email alerts
|

ON THE IONIZATION OF LUMINOUSWMAPSOURCES IN THE GALAXY: CONSTRAINTS FROM He RECOMBINATION LINE OBSERVATIONS WITH THE GBT

Abstract: The Wilkinson Microwave Anisotropy Probe (WMAP) free-free foreground emission map is used to identify diffuse ionized regions (DIR) in the Galaxy (Rahman & Murray 2010). It has been found that the 18 most luminous WMAP sources produce more than half of the total ionizing luminosity of the Galaxy. We observed radio recombination lines (RRLs) toward the luminous WMAP source G49.75−0.45 with the Green Bank Telescope near 1.4 GHz. Hydrogen RRL is detected toward the source but no helium line is detected, implying … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 44 publications
0
14
1
Order By: Relevance
“…They find that He I/Hα is significantly reduced only for low escape fractions (∼ 15%). This result is in disagreement with Roshi et al (2012), who observed a N ( 4 He + )/N (H + ) upper limit of only 0.024 in the diffuse gas near the H II region G49, despite an apparent escape fraction of ∼ 63% and N ( 4 He + )/N (H + ) ratios of > 0.066 within the H II region (Churchwell et al 1974;Lichten et al 1979;Thum et al 1980;McGee & Newton 1981;Mehringer 1994;Bell et al 2011). Clearly, a larger sample size is required for further study.…”
Section: Introductioncontrasting
confidence: 75%
“…They find that He I/Hα is significantly reduced only for low escape fractions (∼ 15%). This result is in disagreement with Roshi et al (2012), who observed a N ( 4 He + )/N (H + ) upper limit of only 0.024 in the diffuse gas near the H II region G49, despite an apparent escape fraction of ∼ 63% and N ( 4 He + )/N (H + ) ratios of > 0.066 within the H II region (Churchwell et al 1974;Lichten et al 1979;Thum et al 1980;McGee & Newton 1981;Mehringer 1994;Bell et al 2011). Clearly, a larger sample size is required for further study.…”
Section: Introductioncontrasting
confidence: 75%
“…This hypothesis is supported by wide area RRL mapping at ∼15 resolution (Alves et al 2012) which finds that the distribution of the diffuse medium is correlated with HII regions. However, constraints on the ionising spectrum from He RRLs are not fully consistent with this hypothesis (Roshi et al 2012). Thus higher resolution observations of H RRLs and more sensitive observations to detect He RRLs are required.…”
Section: Early Science: the Structure And Kinematics Of The Most Lumimentioning
confidence: 99%
“…Helium lines are typically ∼8 percent of the brightness of Hydrogen RRLs, but are valuable tracers of both the metallicity of the ionised gas (e.g. Balser et al (2001)) and the hardness of the illuminating UV spectrum (Roshi et al 2012). More than 90% of the observed 4 He in the ISM of the Milky Way was produced via primordial nucleosynthesis (Wilson & Rood 1994).…”
Section: Pos(aaska14)126mentioning
confidence: 99%
“…It is therefore suggested that using a completely different observing technique may be the best way to address the problem, at least empirically (see for example Roshi et al, 2012). This is especially true when the problem is now reduced simply to one of determining whether the linewidths in question are stronger and narrower than predicted.…”
Section: Future Workmentioning
confidence: 99%